2012
DOI: 10.2174/1876524601205010001
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Recurrent Hypoglycemia Markedly Impairs Set-Shifting Ability in a Rodent Model: Cognitive and Neurochemical Effects

Abstract: Recurrent hypoglycemia (RH) is the major complication of intensive insulin treatment for diabetes mellitus. Of particular concern is the perceived potential for long-term impact of RH on cognition. Because diabetic patients have been reported to have deficits in mental flexibility and judgment, both generally considered to be mediated predominantly by the prefrontal cortex, the purpose of the present study was to determine whether RH would affect prefrontal cortex function. Medial prefrontal cortex (mPFC)-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Taken together with our previous studies, the findings here indicate that RH affects multiple neural systems and brain structures, with the impact of RH varying by region and system. For instance, during subsequent euglycemia, RH enhances hippocampal memory ( 22 , 23 ), impairs mental flexibility processes in the prefrontal cortex ( 24 ), but does not affect performance in an elevated plus-maze test of anxiety (present data). The ability of a rodent model of RH to accurately mimic many of the cognitive effects seen in human patients after RH suggests that this is an appropriate system for further studies aimed at identifying the molecular mechanisms transducing the cognitive, neural, and metabolic impact of RH, with a goal of identifying appropriate therapeutic approaches to prevention and intervention.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Taken together with our previous studies, the findings here indicate that RH affects multiple neural systems and brain structures, with the impact of RH varying by region and system. For instance, during subsequent euglycemia, RH enhances hippocampal memory ( 22 , 23 ), impairs mental flexibility processes in the prefrontal cortex ( 24 ), but does not affect performance in an elevated plus-maze test of anxiety (present data). The ability of a rodent model of RH to accurately mimic many of the cognitive effects seen in human patients after RH suggests that this is an appropriate system for further studies aimed at identifying the molecular mechanisms transducing the cognitive, neural, and metabolic impact of RH, with a goal of identifying appropriate therapeutic approaches to prevention and intervention.…”
Section: Discussionmentioning
confidence: 48%
“…In studies to date, RH in our model has not impaired or reduced motor activity, visual acuity, or, e.g., motivation: for example, RH animals make the same number of maze-arm choices ( 22 , 23 ), have the same latency to seek reward ( 24 ), and perceive both visual and textural stimuli as well as or better than control animals ( 24 ). We confirmed that RH had no measureable effects on motor performance, motivation, or sensory acuity using small separate cohorts of animals, treated identically to those reported here and tested on a simple Y-maze alternation task.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…However, this possibility remains speculative in the absence of confirmatory protein assay or histochemical analysis. It is noteworthy that recurrent moderate hypoglycemia leads to dampening of PFC activation in the post-hypoglycemia period in adult rats [49,50]. …”
Section: Discussionmentioning
confidence: 99%